Efeitos sedativos e cardiorrespiratórios da dexmedetomidina isolada ou associada à acepromazina em felinos saudáveis - Schimites, Paula Ivanir (2024)
This thesis was divided into two sections. The first section refers to a retrospective study manuscript of anesthetic records in felines from February 2022 to February 2023, carried out at the Veterinary University Hospital of the Federal University of Santa Maria - RS, with the aim of determining the frequency of dexmedetomidine's use, possible associations with other drugs, dose used and the impact on dose reduction of other anesthetics. A total of 358 medical records were analyzed, of which 126 (35%) had protocols with dexmedetomidine (median dose of 4.0 µg/kg) alone (9/126 cases, 7%) or in association with drugs such as opioids and dissociatives ( 55/126 cases, 44%), followed by the association with opioids only (49/126 cases, 39%), associated with dissociatives only (6/126 cases, 5%) and other less frequent associations. According to the study, there was no influence of the protocol used as preanesthetic medication on the need or not to use doses higher than 3 mg/kg of propofol for anesthetic induction in felines sedated with dexmedetomidine associated or not with other pharmacological classes and with or without the use of co-inducers. According to the study, there was no influence of the protocol used as pre-anesthetic medication on the need or not to use doses higher than 3 mg/kg of propofol for anesthetic induction in felines sedated with dexmedetomidine associated or not with other pharmacological classes and with or without the use of co-inducers. The second section refers to a published scientific article that aimed to investigate the sedative potential, incidence of emesis and cardiovascular changes in two groups of healthy felines submitted to outpatient sedation with dexmedetomidine alone or associated with acepromazine. Fourteen healthy adult male felines were included in the study, divided into two experimental treatments: GD (dexmedetomidine 5 µg/kg IM, n=7) and GDA (dexmedetomidine 5 µg/kg + acepromazine 0.03 mg/kg IM, n=7), with the volume of the treatments diluted with NaCl 0.9% to a total of 0.5 mL. Assessments began 20 minutes after sedation by a blinded evaluator, who recorded sedation scores (0 = no sedation; 1 = able to remain standing but staggering; 2 = sternal recumbency; 3 = able to raise head; and 4 = lateral recumbency unresponsive to clapping), episodes of emesis, heart rate (HR), respiratory rate (FR), rectal temperature, and systolic arterial pressure (SAP). The variables were collected at 20 minutes after sedation and every 10 minutes until they returned to baseline levels. At baseline and at T30, venous blood samples were collected for blood gas analysis. At T20, HR was significantly lower in GDA compared to GD and SAP was significantly lower in both groups compared to baseline. The time of sedation was similar between groups, although sedation scores differed significantly at T20, with 1 (0–4) in GD and 4 (4–4) in GDA. More episodes of emesis were recorded in GD compared with GDA. The combination of dexmedetomidine and acepromazine produced deeper sedation with faster onset and a lower incidence of emesis compared with dexmedetomidine alone in healthy cats. The results of this thesis will certainly enrich the scientific literature and contribute to advances and updates in veterinary anesthesiology. Studies will be necessary to evaluate reproducibility for clinical use in hospital routine not just in healthy patients.